Pelestarian Pakaian Adat Melayu Riau Bagi Remaja di Provinsi Riau : Budaya Melayu Riau - Novendri Putra; Sri Wahyuningsih; Rizky Fatya Amanda; Juliani, Juliani; Yunda Hasbi Pratama (Yayasan Literasi Sains Indonesia, 2024)
Riau Province is an Indonesian province located on the east coast of the central island of Sumatra. Its coastal area borders the Strait of Malacca. Until 2004, the province also included the Riau Islands, a large group of small islands (the main islands include Batam Island and Bintan Island) located east of Sumatra and south of Singapore. The archipelago was split into its own province in July 2004. The capital and largest city in Riau province is Pekanbaru, and the other major city after Pekanbaru is Dumai. Riau is currently one of the richest provinces in Indonesia, and its resources are dominated by natural resources, especially petroleum, natural gas, rubber, oil palm and fiber plantations. along with the abundance of natural resources, Riau is also famous for its rich traditions and culture, both physical and non-physical that are inherent in the Riau people themselves. one of the physical cultures in Riau is Riau Malay traditional clothing. The people in Riau are dominated by the Malay tribe, where this tribe is also influenced by the Malay culture in Sumatra, Malaysia, Singapore. due to the close proximity of the region. characterized by similarities in dress or dress that has its own characteristics. the people of Riau usually wear their traditional clothes at major events, such as traditional ceremonies, holidays, official events.